Value of cervical mediastinoscopy, parasternal left mediastinotomy and spiral CT in NSCLC patients qualified to surgical treatment - Dzięgielewski, Piotr; Łapuć, Grzegorz; Cybulski, Adam; Gułaj, Cezary; Laudański, Wojciech; Laudański, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : NSCLC patients still have bad prognosis among overall cancer disease cases. New approaches in diagnosis and treatment are insufficient as yet, and better TNM classification algorithms based on viable and invasive staging methods together are needed. Aim : The aim was to evaluate mediastinoscopy together with parasternal mediastinotomy in mediastinal lymph nodes detection and comparison with spiral CT, measurement of clinical TNM patient down- and over-staging. Material and methods : 143 consecutive NSCLC patients received chest CT, mediastinoscopy and 10 patients additionally parasternal left mediastinotomy, with enlarged and normal mediastinal lymph nodes as well. Clinical TNM staging before and after invasive staging was performed. We calculated and compared sensitivity, specificity, accuracy, positive and negative predictive value of CT and invasive procedures. Results : Surgical methods were always much better than CT in mediastinal lymph nodes assessment on a “per patient” and “per nodal” station basis as well, mainly due to its high accuracy (93%), 100% specificity and high negative predictive value (92.3%) vs. TK results: 39%, 29.5%, 74.2% respectively. If CT is a sufficient tool for T status evaluation, then in N2 disease it should be completed with an invasive method. Conclusions: Mediastinal CT is an unreliable method that must be accompanied by an invasive procedure. Patients in early NSCLC stages should more often have invasive evaluation of mediastinum due to 17% of micrometastases, especially in adenocarcinoma.